Pendugaan Cadangan Karbon Above Ground Biomass (AGB) pada Tegakan Sawit (Elaeis guineensis Jacq.) di Kabupaten Langkat / (The Estimate of Carbon Stocks Above Ground Biomass (AGB) on Palm (Elaeis guineensis Jacq.) Stands in Langkat District) - Kepler Dopler Purba; Rahmawaty Rahmawaty; Riswan Riswan (Peronema Forestry Science Journal, 2013)
Palm Oil Plant a CO2 absorber as well as other crops such as forest plants. Langkat District is one of the areas that have a high oil commodity. Research on AGB estimates carbon stocks in standing palm (Elaeis guineensis Jacq) in Langkat conducted in July through September 2012. This study uses Allometric that calculate carbon stocks in standing palm (Elaeis guineensis Jacq.) Associated with the value of Normalized Difference Vegetation Index (NDVI).Largest carbon stocks contained in the 14-year-old stands of oil reserves by 68.84 tonnes carbon / ha and the smallest carbon stocks contained in the 3-year old palm stands by the number of carbon reserves 19.20 tonnes / ha. Vegetation index can be calculated by the model equation Y = 38.39 + 26.24 x NDVI on Landsat imagery. NDVI has a positive relationship with the value of the field in which the R ² of the resulting equation is equal to 49% of the stands of palm oil (Elaeis guineensis Jacq.). Keywords: Carbon stock estimate, Above Ground Biomass, Palm Stands, Elaeis guineensis Jacq.